FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI PETANI DI KAWASAN TAMAN NASIONAL LORE LINDU (TNLL) UNTUK MENCARI ROTAN (Studi Kasus di Desa Doda Kecamatan Lore Tengah Kabupaten Poso) - Antara, Made (FAPETKAN UNTAD, 2005)
This research work aimed at studying social economic factors influencing farmers go to the forest to gather cane. Doda village was chosen as sample village and sample in Doda village. 43 people was randomly sample to be interviewed. The data obtained showed that low income, big size of family, small size land owned, and having experience in gathering cane all were factors that urged farmers o gather cane. In contrast, formal education was found not to be associated with farmers gathering cane.Key words : Income, socio-economics, cane and multiple regression analysis